PENEGAKAN HUKUM TINDAK PIDANA POLITIK UANG PEMILIHAN UMUM LEGISLATIF PADA MASA KAMPANYE DI KABUPATEN SERANG (Jurnal Hukum Mimbar Justitia, 2016)
Regarding to the democracy as the people's sovereignty, the general election of 2014 was held by the aim to select a representative. The aim of this study is to determine whether there is criminal offense of money politics in Serang district during the legislative electoral campaign according to the regulation no. 8 of 2012 on the General Election of DPR, DPD and DPRD. This research was conducted by using juridical empirical approach directly to the committee electoral supervisor of Serang District as the result of violations that was reported by the committee electoral supervisors during campaigns, involving children under the age and money politics, but in fact most of the violations are money politics. Modes of money politics violation that committed by legislative candidates in Serang are (1) Direct money politics in the form of cash or stuffs by legislative candidates or successful teams; (2) Indirect money politics in form of distributing foods such as rice, noodles, vegetable oil, eggs and others; promising grants for a group or individual. The identification of the problem are 1) How the law enforcement against criminal acts of money politics fulfills the legal certainty? 2) What types and forms of acts that can be qualified as criminalization of money politics during the campaign? In fact, to prove money politics cases in Serang is difficult, because of insufficient evidence, political constraints of money politics violations in general election of law enforcement in Serang, electoral supervisor having trouble in finding evidence of violations of electoral money politics and lack of attention from environment, the need for political education, and encouragement and fair of law enforcement officers.Keywords: General Election, Money Politics, Criminalism, Law Enforcement.